PS6:109 Association of mental health related quality of life (hrqol) and subsequent physical functioning in systemic lupus erythematosus: analysis of data from the german lula cohort 2002 – 2013. (21st March 2018) - Brinks, R; Chehab, G; Fischer-Betz, R; Richter, J; Willers, R; Winkler-Rohlfing, B; Schneider, M
Abstract : Introduction: Mental symptoms are a major problem in patients with systemic lupus erythematosus (SLE). From geriatric patients it is well-known that prevention of mental disorders leads to maintenance of physical functioning (PF). Methods: Data from the German Lupus-Langzeitstudie (LuLa) open cohort was used to explore the effect of self-reported mental HRQoL on PF. The ongoing LuLa study comprises patients from the German SLE self-help group. The current analysis uses data from 2002 to 2013. We looked for associations between the PF score (outcome) and the mental component summary (MCS) score (exposure) of the SF-12 questionnaire in one to four years preceding the outcome. Statistical analysis was accomplished by a linear mixed regression model (LMM) adjusting for the potential confounders age, sex, disease duration and disease activity as surveyed by the Systemic Lupus Activity Questionnaire score (SLAQ). Results: 1511 patients (93.3% women) provided data with a total of 7841 person-years of observation. Median age at study entry was 46 (interquartile range: 37 to 57). Table 1 shows the regression coefficients of MCS (and 95% confidence intervals, CI) estimated by the LMM without and with adjusting for age, sex, disease duration and SLAQ. Conclusions: We found evidence that self-reported mental HRQoL in patients with SLE is associated with PF in the subsequent years. The data indicate a 'window of opportunity' for treating mental symptoms of up to three years for maintenance of PF.